1960
DOI: 10.1017/s0021859600023303
|View full text |Cite
|
Sign up to set email alerts
|

The total digestible nutrients and gross digestible energy of ruminant feeds

Abstract: It is shown that reasonable estimates of the average amounts of total digestible nutrients and gross digestible energy of ruminant feeds can be derived from knowledge of only the crude-protein and crude-fibre contents of such material as fed. These estimates do not appear to be markedly affected, if at all, by differences in class of feed or species of ruminant whether cattle, sheep or goat.A table of the average estimates of digestible crude protein and total digestible nutrients, to be expected at different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2000
2000

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Forage quality during the dry season falls below maintenance requirements of the animals with a resulting depletion of body reserves; these reserves are replenished during the wet season (Sinclair and Duncan 1972;Sinclair 1974aSinclair , 1974b. It is well known that forage quality diminishes with plant tissue age (Glover et al 1960;Armstrong et al 1964;Miller et al 1965;Braun 1973) and that higher quality forage not only gives a higher nutritional yield, but can be consumed in larger quantities by ruminants (Hungate 1975). Thus, apparent overcropping by wildebeest probably maintains higher nutritional yield than would less intense grazing, allowing more rapid replenishment of body reserves than would consumption of larger quantities of lower quality forage (Baile and Forbes 1974;Hungate 1975).…”
Section: Resultsmentioning
confidence: 99%
“…Forage quality during the dry season falls below maintenance requirements of the animals with a resulting depletion of body reserves; these reserves are replenished during the wet season (Sinclair and Duncan 1972;Sinclair 1974aSinclair , 1974b. It is well known that forage quality diminishes with plant tissue age (Glover et al 1960;Armstrong et al 1964;Miller et al 1965;Braun 1973) and that higher quality forage not only gives a higher nutritional yield, but can be consumed in larger quantities by ruminants (Hungate 1975). Thus, apparent overcropping by wildebeest probably maintains higher nutritional yield than would less intense grazing, allowing more rapid replenishment of body reserves than would consumption of larger quantities of lower quality forage (Baile and Forbes 1974;Hungate 1975).…”
Section: Resultsmentioning
confidence: 99%
“…In the present series of experiments, no prediction of the content of DE of the various forages could be made from chemical composition. Glover, Duthie & Dougall (1960) have given an equation Saccharinum officinarum (Sugar cane tops) * Trial no. refers to the trial number used in a previous publication (Butterworth, 1963 relating DE with CF and CP (depending on TDN), and Walker & Hepburn (1955) have shown that DE is closely related to CF.…”
Section: Discussionmentioning
confidence: 99%
“…is proportional to the % c.p. in the herbage; while Glover, Duthie & Dougall (1960) show that the total feed digestibility falls rapidly as the c.p. content drops below 5 %.…”
Section: Discussionmentioning
confidence: 97%